Studying of preconditions of introduction of integrating-utilizing balls in the process of physical education of children of the senior preschool age - Pasichnyk V. M. (Kharkov National Pedagogical University, 2012)
The condition of introduction of integrating-utilizing balls in process of physical education of children of the senior preschool age is considered. In research is used the data of questionnaire of 95 teachers of preschool educational establishments of Lvov. It is established that all interrogated are interested in innovations in physical education process. It is noticed that the majority of respondents 54, 6 % prefer sports employment with elements of games, entertainments and relay races. Determined that 72, 9 % interrogated combined sports employment with other subjects. It is shown that impellent activity promotes mental development of children. By the overwhelming majority of respondents of 98, 8 % are noticed that in the course of physical education it is expedient to combine impellent and informative activity. It is established that all respondents would like to introduce is integrating-utilizing balls in process of physical education of the pre-school educational establishments and see expedient working out of methodical recommendations.